Microstructural Characteristic Of Lateritic And Marine Clay Soil - Alias, Ahmad Danish Ab (Universiti Sains Malaysia, 2021)
Soil conditions will always vary as a reaction to weather, composition, and age. As a result of such changes, it may contribute to either the favourable or unfavourable state of the soil. A good ground foundation is required for a solid construction foundation. Lateritic soil and marine clay soil used as soil samples for this investigation are examples of weak soil. It is considered unsuitable due to the visible presence of high moisture content. It often occurs as a slurry, including a considerable amount of expandable clay minerals. Working with marine clay soil is extremely difficult owing to its strong impact on moisture content. The physical qualities of the soil influence its strength and stability. Soil with a high capacity and structure is more stable. When it comes to soil, an admixture is a substance implemented to enhance soil characteristics, structure, and ability. For the stabilizing admixture materials, cement and lime were selected. Standard Proctor test is a compaction test that will determine the effects of these stabilizing materials toward the compaction process for their density and moisture content results. The effects of cement and lime are majorly focused on the moisture content. Higher cement and lime composition give less moisture content to achieve maximum dry density, while lime results from using up an existing moisture content to perform the pozzolanic reaction. The reaction alters the microstructure of the treated soil. Theoretically, both stabilizing agents consist of the same reaction outcomes. This research and findings will contribute to extra knowledge on understanding the mechanism of stabilizing materials.